2023
DOI: 10.19184/jsb.v11i1.39562
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh sosial media marketing dan influencer marketing terhadap keputusan pembelian konsumen (studi pada konsumen produk kosmetik wardah di Kabupaten Jember)

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh sosial media marketing, influencer marekting terhadap keputusan pembelian konsumen. Jenis penelitian ini menggunakan penelitian kuantitatif. Data yang dikumpulkan dalam penelitian ini menggunakan kuesioner atau memberikan beberapa lembar pernyataan untuk mengumpulkan data responden dengan jumlah responden sebanyak 120 orang. Responden diambil dari konsumen dari konsumen produk Kosmetik Wardah di Kabupaten Jember. Data diolah dengan menggunakan analisis regresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several previous studies by (Sari & Hidayat, 2021); (Lengkawati & Saputra, 2021); dan (Fathurrahman et al, 2021), have concluded that influencer marketing has a positive and significant influence on purchase decisions. Individuals are more likely to make a purchase decision when they see a high number of followers or subscribers of an influencer.…”
Section: The Relationship Between Influencer Marketing and Purchase D...mentioning
confidence: 96%
“…Several previous studies by (Sari & Hidayat, 2021); (Lengkawati & Saputra, 2021); dan (Fathurrahman et al, 2021), have concluded that influencer marketing has a positive and significant influence on purchase decisions. Individuals are more likely to make a purchase decision when they see a high number of followers or subscribers of an influencer.…”
Section: The Relationship Between Influencer Marketing and Purchase D...mentioning
confidence: 96%